Recent advances on the mechanical behavior of zinc based biodegradable metals focusing on the strain softening phenomenon. (15th October 2022) - Huang, He; Li, Guannan; Jia, Qinggong; Bian, Dong; Guan, Shaokang; Kulyasova, Olga; Valiev, R.Z.; Rau, Julietta V.; Zheng, Yufeng
Abstract: Zinc based biodegradable metals (BMs) show great potential to be used in various biomedical applications, owing to their superior biodegradability and biocompatibility. Some high-strength (ultimate tensile strength > 600 MPa) Zn based BMs have already been developed through alloying and plastic working, making their use in load-bearing environments becomes a reality. However, different from Mg and Fe based BMs, Zn based BMs exhibit significant "strain-softening" effect that leads to limited uniform deformation. Non-uniform deformation is detrimental to Zn based devices or implants, which will possibly lead to unexpected failure. People might be misled by the considerable fracture elongation of Zn based BMs. Thus, it is important to specify uniform elongation as a term of mechanical requirements for Zn based BMs. In this review, recent advances on the mechanical properties of Zn based BMs have been comprehensively summarized, especially focusing on the strain softening phenomenon. At first, the origin and evaluation criteria of strain softening were introduced. Secondly, the effects of alloying elements (including element type, single or multiple addition, and alloying content) and microstructural characteristics (grain size, constituent phase, phase distribution, etc.) on mechanical properties (especially for uniform elongation) of Zn based BMs were summarized. Finally, how to get a good balance between strength and uniform elongation was generally discussed based on the service environment. In addition, possible ways to minimize or eliminate the strain softening effect were also proposed, such as controlling of twins, solute clusters, and grain boundary characteristics. All these items above would be helpful to understand the mechanical instability of Zn based BMs, and to make the full usage of them in the future medical device design. Statement of significance: Biodegradable metals (BMs) is a hotspot in the field of metallic biomaterials. Fracture elongation is normally adopted to quantify the deformability of Mg and Fe based BMs owing to their negligible necking strain, yet the strain softening would occur in Zn based BMs, which is extremely detrimental to performance of their medical device. In this review paper, a better understanding the mechanical performance of Zn-based BMs with the term "uniform elongation" instead of "fracture elongation" was depicted, and possible ways to minimize or eliminate the strain softening effect were also proposed, such as twins, solute clusters, self-stable dislocation network, and grain boundary characteristics. It would be helpful to understand the mechanical instability of Zn based BMs and making full usage of it in the future medical device design. Graphical abstract: Image, graphical abstract